Teater Tradisional Melayu Makyong dalam Lintasan Sejarah dan Kekinian Di Sumatera Utara - Wiflihani, Wiflihani; Suharyanto, Agung (Universitas Negeri Medan, 2014)
The Makyong traditional theatre is a Malayan performing art belong to the indigenous Malays people in North Sumatra, which is knownly originated from Malaysia and Thailand. It was acculturated intimately with the North Sumatra malay costums since had been develop-ped and staged by Royal of Serdang Sultanate. The traditional theatre then had become a entertainment form by for the people in which it performed entertainly and comical staging for refreshing the audience. Nowadays it is a folk art form whichÂ has revived by urban community that performs humors and jokes as the dominant feature in the show. It is staged by spend approxi-mately one and a half hour where it becomes more fascinated in watching in term merely several aspect such as artistics, meanings, symbols, and other which are trapped audience in hard thougth.